Pengaruh Budaya Organisasi Dan Pengembangan Karier Terhadap Disiplin kerja Dengan Kepuasan Kerja Sebagai Variabel Mediasi - -, Harnoto; -, Fasochah (LPPM STIE DHARMAPUTRA SEMARANG, 2013)
Path analysis result shows that indirect influence of organization culture towards work dicipline or p6=0,207 more than direct influence of organization culture towards work dicipline or p4=0,141.This matter proves hypothesis (H6) that organization culture positive influential towards work dicipline with job satisfaction as intervening variable. Indirect influence of career development towards work dicipline or p7=0,250 more than direct influence of oraganization culture towards work dicipline or p5=0,162. This matter proves hypothesis (H7) that career development influential positive towards work dicipline with job satisfaction as intervening variable)Keyword : Organization culture,career development,job satisfaction, work dicipline.